Analyse du parcours d’un élève « multi-dys » : être inclus ou s’inclure ? - Anne Dizerbo (Éducation et Socialisation)
This paper is based on a research in the field of biographical research in education and is interested in school inclusion as a process at the intersection between institutional prescriptions and the individual life courses of the participants involved. It focuses on the case of a pupil in ordinary school, who suffers from several « dys» disorders, memory problems and rapid cognitive overload, and is based in particular on interviews with him and his mother. The analysis of his life course allows us to investigate the conditions, levers, and environments favorable to his inclusion, to the development of a feeling of well-being and to the construction of a capacity to interact with his environment, thus leading to a reflection on the challenges of valuing the expertise of the parents who assist their disabled child on a daily basis and on the narrative models available to the latter to elaborate his own life story.